SDR9C7 plays an essential role in skin barrier function by dehydrogenating acylceramide for covalent attachment to proteins. Issue 2 (May 2020) - Takeichi, Takuya
Highlights: The corneocyte lipid envelope is extremely important for the skin barrier. SDR9C7 catalyzes the dehydrogenation of the lipoxygenase products esterified in CerEOS. SDR9C7 plays a role in the covalent binding of corneocyte lipid envelope to proteins. Abstract: Among the components of the barrier structure of the stratum corneum in human skin, the corneocyte lipid envelope (CLE) is extremely important for the skin barrier. The importance of the CLE and esterified ω-hydroxy sphingosine (CerEOS), its main precursor, has been suggested from the fact that mutations in a number of genes involved in CerEOS synthesis and CLE formation have been identified as genetic causes of congenital ichthyoses, which are severe genetic skin disorders. However, the molecule/mechanism involved in the covalent binding of CerEOS to proteins on the outer surface of the cornified cell envelope had been a missing part. Very recently, we proposed new potential modes of protein binding by covalent reactions of CerEOS-epoxy-enone. We revealed the biochemical function of short-chain dehydrogenase/reductase family 9C member 7 (SDR9C7), encoded by SDR9C7, as catalyzing the dehydrogenation of the lipoxygenase products that are esterified in CerEOS. Epoxy-enone produced by SDR9C7 covalently binds to proteins on the outer extracellular surface of the cornified cell envelope. Importantly, our recent striking findings were derived from the detailed lipid analysis of only one ARCI patient with SDR9C7 mutation. The combination of detailed analyses of precious samples from a rare patient and the establishment of corresponding animal models is an effective and powerful tool for analyzing rare inherited diseases. This review summarizes this newly revealed mechanism in skin barrier formation, describes the characteristic features of patients with SDR9C7 mutations, and introduces the clinical value of non-invasive analyses for patients with very rare intractable skin diseases.